Pentingnya Literasi Keuangan Bagi Siswa Siswi Di SMK PGRI 31 Legok Kabupaten Tangerang - Aldi Samara; Rr Dian Anggraeni; Rina Sulistyowati (Pusat Riset dan Inovasi Nasional, 2024)
Recently, people have been shocked by the high level of bad credit among Millennials. Based on the findings of the Otoritas Jasa Keuangan (OJK) (Wibowo, 2024), the number of bad loans for more than 90 days in the peer-to-peer (P2P lending) financial technology industry, or what is known as loans for the individual category, has reached IDR 1,73 trillion as of May 2023. The problem is, the Millennial generation or those aged 19-34 years are the biggest